Magnetless Device for Conducting Three‐Dimensional Spin‐Specific Electrochemistry. (18th October 2017) - Kumar, Anup; Capua, Eyal; Vankayala, Kiran; Fontanesi, Claudio; Naaman, Ron
Abstract: Electron spin states play an important role in many chemical processes. Most spin‐state studies require the application of a magnetic field. Recently it was found that the transport of electrons through chiral molecules also depends on their spin states and may also play a role in enantiorecognition. Electrochemistry is an important tool for studying spin‐specific processes and enantioseparation of chiral molecules. A new device is presented, which serves as the working electrode in electrochemical cells and is capable of providing information on the correlation of spin selectivity and the electrochemical process. The device is based on the Hall effect and it eliminates the need to apply an external magnetic field. Spin‐selective electron transfer through chiral molecules can be monitored and the relationship between the enantiorecognition process and the spin of electrons elucidated.